C-O hydrogenolysis of C3-C4 polyols selectively to terminal diols over Pt/W/SBA-15 catalysts - Bhowmik, Susmita; Enjamuri, Nagasuresh; Marimuthu, Banu; Darbha, Srinivas (Catalysts, 2022)
Pt/W/SBA-15 catalysts (with Pt-loading = 0.5-4 wt% and W-loading = 1 wt%) prepared by the sequential impregnation method were evaluated for selective C-O cleavage of erythritol and glycerol in an aqueous medium. The Pt and W particles dispersed on SBA-15 approached close proximity at higher Pt loadings and afforded synergistic enhancement in C-O hydrogenolysis activity/selectivity. 1,4-Butanediol yields of 30.9% (at 190 degrees C, 50 bar H-2 and 24 h) and 1,3-propanediol yields of 34.4% (at 190 degrees C, 50 bar H-2 and 12 h of reaction) were obtained over these catalysts. Pt nanoparticles (facilitating dissociative H-2 adsorption and spillover) and W (present as acidic oligomeric WOx species; activating and coordinating the polyol via 1 degrees-OH group) worked in tandem for the selective hydrogenolysis of polyols yielding terminal diols of industrial demand.
Keywords: diol; Erythritol; Glycerol; Hydrodeoxygenation; Pt; SBA-15; W